Konstruksi Qira'ah I'jaziyyah ân al-Qur`an M. Abdullah Darraz - Intizham, Kemas Muhammad; Saputra, Adang (Aqwal: Journal of Qur'an and Hadis Studies, 2021)
This article tries to describe the M. Abdullah DarrÄzâ€™s toughts on iâ€™jÄz al-Qur`Än as basic of reading-cum-understanding on the Qur`Än. Initially, the discussion of iâ€™jÄz al-Qur`Än started from debate among the scholars about theological doctrines on the Qur`Än such as al-muâ€™Äraá¸ah, at-taá¸¥addÄ«, tark al-muâ€™Äraá¸ah, and al-â€™ajz. But, DarrÄz was able to discussed the discourse of iâ€™jÄz into domain of Qur`anic interpretation, and also Qur`anic reception in his work: an-NabÄ` al-â€™Aáº“Ä«m: Naáº“arÄt JadÄ«dah fÄ« al-Qur`Än. Through his work, DarrÄz was able to formulated the principles of reading-cum-understanding on the Qur`Än are sourced from its iâ€™jÄzâ€”which I term it with qirÄ`ah iâ€™jÄziyyah â€™an al-Qur`Änâ€”such as principle of coherence, intertextuality and stylistics of the Qur`Än.